PENGARUH KOMPETENSI PEDAGOGIK DAN DISIPLIN KERJA TERHADAP KINERJA GURU MELALUI MOTIVASI KERJA PADA SMP NEGERI 5 PENAJAM PASER UTARA KALIMANTAN TIMUR - Sahria, Sahria (Program Pascasarjana Universitas Wijaya Putra Surabaya, 2023)
This research is to analyze the influence of pedagogical competence and work discipline on teacher performance through work motivation at SMP Negeri 5 Penajam Paser Utara, East Kalimantan. This type of research is explanatory with a quantitative approach and data analysis techniques using path analysis. The research sample was 49 teachers, hereinafter referred to as respondents. Pedagogical Competency has a significant effect on Teacher Work Motivation at SMP Negeri 5 Penajam Paser Utara, East Kalimantan. Work Discipline has a significant effect on Teacher Work Motivation at SMP Negeri 5 Penajam Paser Utara, East Kalimantan. The results of the research show that Pedagogical Competency has a significant effect on Teacher Performance at SMP Negeri 5 Penajam Paser Utara, East Kalimantan. Work Discipline has a significant effect on Teacher Performance at SMP Negeri 5 Penajam Paser Utara, East Kalimantan. Work Motivation has a significant effect on Teacher Performance at SMP Negeri 5 Penajam Paser Utara, East Kalimantan. Teacher Pedagogical Competence has a significant effect on Teacher Performance through Work Motivation at SMP Negeri 5 Penajam Paser Utara, East Kalimantan. Work Discipline has a significant effect on Teacher Performance through Work Motivation at SMP Negeri 5 Penajam Paser Utara, East Kalimantan.